A novel, validated risk score to predict surgical site infection after pancreaticoduodenectomy. Issue 11 (November 2016) - Poruk, Katherine E.; Lin, Joseph A.; Cooper, Michol A.; He, Jin; Makary, Martin A.; Hirose, Kenzo; Cameron, John L.; Pawlik, Timothy M.; Wolfgang, Christopher L.; Eckhauser, Frederic; Weiss, Matthew J.
Abstract: Background: Although pancreaticoduodenectomy (PD) outcomes have improved, complications including surgical site infection (SSI) remain common. We present a stratification tool to predict risk for SSI after PD. Methods: Data was retrospectively reviewed on all patients undergoing PD at a tertiary hospital (9/2011-8/2014). Potential SSI risk factors identified by univariate analysis were incorporated into a multivariate logistic regression model. The resulting odds ratios were converted into a point system to create an SSI risk score with internal validation. Results: Six hundred seventy nine patients underwent PD and were chronologically split into derivation (443 patients) and validation (236 patients) groups. There was no difference in demographics or perioperative outcomes between groups. Overall thirty-day SSI was observed in 17.2% (n = 117). Neoadjuvant chemotherapy and/or radiation, intraoperative red blood cell transfusion, operative time greater than 7 h, preoperative bile stent/drain, and vascular resection were associated with SSI in univariate analysis (all p < 0.05). On multivariate analysis, preoperative bile stent/drain and neoadjuvant chemotherapy were independent predictors of SSI, each assigned 1 point (both p < 0.001). Patients with 0, 1, and 2 points, respectively, had 0%, 32%, and 64% predicted risk of SSI (AUC = 0.73, R 2 = 0.93). The model performed equivalently in the validation group (AUC = 0.77, R 2 = 0.99). Conclusion: This novel, validated risk score accurately predicts SSI risk after pancreaticoduodenectomy. Identifying the highest risk patients can help target interventions to reduce SSI.